In vivo fluctuation of Tax, Foxp3, CTLA-4, and GITR mRNA expression in CD4+CD25+ T cells of patients with human T-lymphotropic virus type 1-associated myelopathy - E. Ramirez; L. Cartier; L. Rodriguez; C. Alberti; M.A. Valenzuela (Brazilian Journal of Medical and Biological Research, 2010)
HTLV-1 Tax expression exerts an inhibitory effect on the Foxp3 transcription factor in CD4+CD25+ T-regulatory cells (Treg). For a better understanding of the role of Tax mRNA in the gene expression of cellular markers we measured Tax, Foxp3, CTLA-4, GITR, TGF-β, and IL-10 mRNA in Treg cells of 50 patients with human T-lymphotropic virus type 1 (HTLV-1)-associated myelopathy/tropical spastic paraparesis (HAM/TSP; 27 women and 23 men; mean age: 56.7 years). The control group consisted of 23 non-infected subjects (12 women and 11 men) with a mean age of 51.3 years. Real-time PCR was used to measure mRNA of Tax proteins and several cellular markers of Treg function. Determinations revealed a high level of Tax mRNA in HAM/TSP (124.35 copies/100 CD4+CD25+ T cells). Foxp3, GITR, and CTLA-4 mRNA levels were lower in HAM/TSP patients (mean ± SD, 22.07 ± 0.78, 9.63 ± 0.36, and 4.54 ± 0.39, respectively) than in non-infected controls (47.15 ± 12.94, 22.14 ± 1.91, and 21.07 ± 2.31). Both groups had similar levels of TGF-β and IL-10. An inverse relationship was found between Tax levels and Foxp3, CTLA-4, and GITR levels. Conversely, there was a direct correlation between levels of Foxp3, GITR, and CTLA-4. Disease severity and evolution time did not correlate with Tax or Foxp3 levels. The present results suggest that Tax and Foxp3 mRNA vary with the same degree of disease severity in HAM/TSP patients. Tax fluctuations may affect CTLA-4 and GITR expression via the Foxp3 pathway, causing virus-induced dysfunction of CD4+CD25+ T cells in HAM/TSP patients.